Does transforming subjective measures of load better represent training and match-play intensity in youth soccer players? - Maughan, P. C.; MacFarlane, N. G.; Towlson, C.; Barrett, S.; Swinton, P. A. (International Journal of Sports Science & Coaching, 2023)
The purpose of this study was to investigate the structure of relationships between measures of training load and assess whether these can be modified through non-linear transformations. Ratings of perceived exertion (RPE) and seven external load measures (total distance covered, PlayerLoad, low-intensity running distance, high-speed running distance, sprinting distance, accelerations, and decelerations) were collected from 20 academy soccer players (age = 17.4 ± 1.3 years, stature = 178.0 ± 8.1 cm, body-mass = 71.8 ± 7.2 kg), with 3220 recordings taken across a 47-week season. To control for the effects of session duration, sessions were categorised as short (=60 min) or long (>60 min). All RPE and sessional RPE-training load (sRPE-TL; RPE multiplied by session duration) were analysed in their raw form and through raising to a series of exponentials. The underlying structure of the data was investigated using principal component analysis. Two components were retained for each analysis and varimax rotation was performed. The first rotated component (RC) was best represented as a measure of volume (RCvolume) with high loadings for RPE and sRPE-TL, whilst the second RC was best represented as a measure of intensity (RCintensity). Non-linear transformations had little effect on loading of modified measures for long sessions for sRPE-TL (RCvolume: 0.87-0.8; RCintensity: 0.27-0.13), and for RPE (RCvolume: 0.76-0.79; RCintensity: 0.17-0.10). For short sessions, the loading became more equal between intensity and volume for sRPE-TL (RCvolume: 0.88-0.41; RCintensity: 0.32-0.36) and more aligned to intensity (RCintensity: 0.52-0.61) compared with volume (RCvolume: 0.44-0.23) for RPE. The present study demonstrates that RPE and sRPE-TL predominantly reflect measures of training volume, however, they can be modified to better reflect intensity for training sessions <60 min in duration.